Building personal branding from the reality of University students using dating apps - Vy, Nguyen Ngoc Thao; Chau, Tran Nguyen Ngoc; Tien, Dinh Hoang; Khang, Nguyen Tan (PRofesi Humas, 2024)
Background: Dating applications are becoming increasingly popular among young people, especially Generation Z students. Purpose: This study investigates the current usage of dating applications among students, specifically those majoring in social sciences and humanities. Methods: The study adopts a mixed-method research design, combining qualitative and quantitative approaches. Qualitative data are collected through a literature review to establish the theoretical framework. Quantitative data are collected through surveys and analyzed using specialized statistical software. Results: The findings indicate that social media is an effective tool for connecting student communities and plays a role in introducing and promoting dating applications. The trend of using dating applications among students is widespread, reflecting a growing demand among Generation Z for establishing romantic relationships through online platforms rather than traditional face-to-face meetings. Conclusion: Social media plays a significant and indispensable role in the mental life of students. Through social networks, students learn about and can access dating applications. Online dating is a new and modern trend compared to traditional dating methods, offering opportunities and risks due to its novelty. Implications: The study sheds light on the usage patterns of dating applications among students and reveals diverse motivations behind their usage, ranging from seeking romantic relationships to fulfilling social connection and entertainment needs.